Maturation of subtilisin-like protease NbSLP1 from microsporidia Nosema bombycis - Wang, Rong; Li, Qingyan; Liu, Fangyan; Dang, Xiaoqun; Sun, Quan; Sheng, Xiaotian; Hu, Mingyu; Bao, Jialing; Chen, Jie; Pan, Guoqing; Zhou, Zeyang (Frontiers in Cellular and Infection Microbiology, 2022)
Microsporidia are obligate intracellular parasites and possess a unique way of invading hosts, namely germination. Microsporidia are able to infect almost all animal cells by germination. During the process, the polar tube extrude from the spore’s within thus inject infectious sporoplasm into the host cells. Previous studies indicated that subtilisin-like protease 1 (NbSLP1) of microsporidia Nosema bombycis located at polar cap of germinated spores where polar tube extrusion. We hypothesized that NbSLP1 is an essential player in germination process. Normally, SLP need to be activated by autoproteolysis under conditions. In this study, we found that the signal peptide of NbSLP1 affected the activation of protease, two self-cleavage sites were involved in NbSLP1 maturation between Ala104Asp105 and Ala124Asp125 respectively. Mutants at catalytic triad of NbSLP1 confirmed the decreasing of autoproteolysis. This study demonstrates that intramolecular proteolysis is required for NbSLP1 maturation. The protease undergoes a series of sequential N-terminal cleavage events to generate the mature enzyme. Like other subtilisin-like enzymes, catalytic triad of NbSLP1 are significant for the self-activation of NbSLP1. In conclusion, clarifying the maturation of NbSLP1 will be valuable for understanding the polar tube ejection mechanism of germination.